The Impact of Remote Education on University Students at Cadi Ayyad University in Morocco: Situation and perceptions - Iflahen, Fatima-Zohra; Benkhallouq , Fatima-Zohra (Environment-Behaviour Proceedings Journal, 2022)
This study analyzes the impact of remote education on the students of open-access institutions affiliated with Cadi Ayyad University in Marrakech, Morocco. This study is based on the collection of qualitative and quantitative data from questionnaires answered by 1760 students, 193 professors and 51 administrative executives. To ensure a better understanding of the impacts of the pandemic on a context afflicted by vulnerability, this study chooses four focal points to its analysis of remote education’s impact on the aforementioned population: Perceptions, Costs, Student Experience and Attendance. In so doing, this study encourages the production of scholarship on educational experiences in times of crisis in Global South countries. Keywords: Remote Education; Lockdown; Higher-Education; UCA. eISSN: 2398-4287 © 2022. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians/Africans/Arabians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/ebpj.v7i19.3195